In vitro exposure to CPF affects bovine sperm epigenetic gene methylation pattern and the ability of sperm to support fertilization and embryo development. (26th October 2018) - Pallotta, Maria Michela; Barbato, Vincenza; Pinton, Alain; Acloque, Hervè; Gualtieri, Roberto; Talevi, Riccardo; Jammes, Hèléne; Capriglione, Teresa
Abstract : Several studies have demonstrated that overexposure to pesticides can reduce mammalian sperm quality, impairing male fertility. Chlorpyrifos (CPF), a widely used organophosphate pesticide, was shown to impair spermatogenesis by inducing the formation of highly reactive toxic intermediates. To gain further insight into the mechanisms underlying the cytotoxicity and genotoxicity of CPF, bovine spermatozoa were exposed in vitro to environmental CPF concentrations and the motility, in vitro fertilization rates, DNA fragmentation, chromatin alterations, and methylation patterns were assessed. Motility and in vitro fertilization rates were significantly reduced in spermatozoa exposed to CPF, while DNA fragmentation and putative chromatin deconstruction appeared to increase at higher pesticide concentrations. In situ hybridization was carried out with X and Y probes on sperm samples exposed to different CPF concentrations, and subsequent analysis highlighted a significant percentage of spermatozoa with a peculiar morphological malformation, in which a narrowing occurred at the level of the hybridization. Analysis of potential abnormalities in the methylation pattern of NESP55‐GNAS and XIST promoters displayed no differentially methylated regions in GNAS promoter relative to the control, whereas spermatozoa exposed to 10 μg/mL CPF had increased methylation variance in one region of imprinted XIST promoter. Our results provide support that CPF can induce a genotoxic effect on spermatozoa, impairig their ability to fertilize and support preimplantation embryo development in vitro . These observations are worrying since altered levels of sporadic methylation in genes of male gametes may affect the success of reproduction and contribute to infertility. Environ. Mol. Mutagen. 60:85–95, 2019. © 2018 Wiley Periodicals, Inc.